Penerapan Data Mining Dalam Menentukan Pola Penjualan Sepatu Menggunakan Algoritma FP-Growth - Syahriani Syahriani (JURIKOM (Jurnal Riset Komputer), 2022)
The company PT Global Vision is a contemporary shoe supplier company, where its shoe products are very popular with young people, children or the elderly. This company provides imported and local shoe products. The owner of the PT Global Vision company wants this company to continue and survive in the midst of increasingly fierce competition and declining people's purchasing power. It should also be noted that this company does not yet have a specific reference or guideline in increasing the company's turnover through the business strategy it implements, in other words, this company still relies on estimates. Therefore, this research was made with the aim that the company PT Global Vision can find out about the working system of shoe sales transactions using the FP-Growth algorithm. Where shoe sales transaction data is used to obtain products that are purchased simultaneously. Then the FP-Growth Algorithm is used to get a combination of product patterns. Meanwhile, FP-Tree is used in conjunction with the FP-Growth algorithm to determine frequent itemset from a database. For the Association rule method itself, it is used to search for patterns of product linkages for sales strategies in decision-making policies, where later it can be known what shoe brands are often purchased by consumers. This can be used as a guideline by PT Global Vision in determining marketing strategies for the next period